Prediction of pre-diabetes and type 2 diabetes nine years postpartum using serum metabolome in pregnant women with gestational diabetes requiring pharmacological treatment - Huhtala Mikael S.; Rönnemaa Tapani; Paavilainen Elisa; Niinikoski Harri; Pellonperä Outi; Juhila Juuso; Tertti Kristiina (Elsevier Inc., 2025)
Aims: We examined the association between serum metabolome in women with pharmacologically treated gestational diabetes (GDM) and measures of glucose metabolism 9 years postpartum.
Methods: Serum targeted metabolome, adiponectin, inflammatory markers, and insulin-like growth factor-binding protein-1 phosphoisoforms were analyzed at the time of diagnosing GDM. Glucose metabolism and insulin resistance were assessed at 9 years postpartum. Data from 119 subjects were available for analyses. Associations between baseline measures and future measures of glycemia were examined with univariate regressions and multivariate prediction models. This is a secondary analysis of a previous prospective trial (NCT02417090).
Results: Baseline serum markers were most strongly related to measures of insulin resistance at 9-years follow-up. In multivariate analyses combination of IDL cholesterol, early gestational weight gain and in oral glucose tolerance test fasting and 2-h glucose predicted development of disorders of glucose metabolism (pre-diabetes and/or type 2 diabetes) better than clinical predictors alone (ROC-AUC 0.75 vs. 0.65, p = 0.020).
Conclusions: Serum metabolome in pregnancy in women with GDM is related to future glucose metabolism and insulin resistance. Compared to clinical variables alone metabolome might result in better prediction of future disorders of glucose metabolism and could facilitate personalized risk stratification for postpartum interventions and follow-up.